Digital trading applications and bank performance: Evidence from Russia - Anton Lisin; Kristina Shvandar; Artur Meynkhard; Mafura Uandykova; Serhat Yüksel; Konstantin Kalmikov; Oleg V. Litviésko; Xenia Tabachkova (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Digital trading apps are evidence of developing open innovations in the financial sector. The investment industry (including banks and brokers) can greatly benefit from the utilization of digital trading applications and corresponding tools, such as smart contracts. The goal of this research paper is to examine the possibility that brokers' existing mobile apps outperform banks without mobile apps in the Russian financial sector. The efficiency of brokers is compared to banks in Russia. The results of these institutions' activities are related to the number of profitable banks, which declines as a sign of high efficiency. The paper uses methods of t-test, linear and polynomial regression analysis between assets (dependent variable) and the profit to assets (independent variable) in Russia. The article finds the different directions of the utilization of the discussed technology, and they all share the consequential growth after the technology's introduction. The paper also discusses the various areas of digital trading apps implementation and the future contributions for the Russian banking system and economy.
Keywords: 650; banks; digital trading apps; distributed ledgers; financial services; smart contracts